2013
DOI: 10.1007/s13659-013-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Five new sucrose esters from the whole plants of Phyllanthus cochinchinensis

Abstract: These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Phytochemical study on the methanol extract of the aerial parts of P. cochinchinensis led to the isolation of four previously undescribed (1)(2)(3)(4) and ten known compounds (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) (Figure 1). The known compounds were identified to be urolignoside (5), [6] 2-[4-[2,3-dihydro-3-(hydroxymethyl)-5-(3-hydroxypropyl)-7methoxy-2-benzofuranyl]-2,6-dimethoxyphenoxy]-1-(4-hydroxy-3-methoxyphenyl)-1,3-propanediol (6), [7] acernikol (7), [8] justicidin B (8), [9,10] restrojusticidin B (9), [10] dehydroguaiaretic acid (10), [11] caliislignan A (11), [12] pinoresinol (12), [13] kaempferol-3-Oβ-D-glucopyranoside (13), [14] isoquercitrin ( 14), [14] by 1D-, 2D-NMR, and ECD spectral data in comparison with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Phytochemical study on the methanol extract of the aerial parts of P. cochinchinensis led to the isolation of four previously undescribed (1)(2)(3)(4) and ten known compounds (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) (Figure 1). The known compounds were identified to be urolignoside (5), [6] 2-[4-[2,3-dihydro-3-(hydroxymethyl)-5-(3-hydroxypropyl)-7methoxy-2-benzofuranyl]-2,6-dimethoxyphenoxy]-1-(4-hydroxy-3-methoxyphenyl)-1,3-propanediol (6), [7] acernikol (7), [8] justicidin B (8), [9,10] restrojusticidin B (9), [10] dehydroguaiaretic acid (10), [11] caliislignan A (11), [12] pinoresinol (12), [13] kaempferol-3-Oβ-D-glucopyranoside (13), [14] isoquercitrin ( 14), [14] by 1D-, 2D-NMR, and ECD spectral data in comparison with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this plant was used to treat dysentery, diarrhea, reduce urination, eczema and scabies [1] . The previous studies have reported the presence of phenolic glycosides, limonoids, and sucrose esters from the whole plant [2–5] . Some of these compounds showed cytotoxicity, anti‐inflammarory, and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations